2014
DOI: 10.3201/eid2001.130774
|View full text |Cite
|
Sign up to set email alerts
|

Novel Avian Coronavirus and Fulminating Disease in Guinea Fowl, France

Abstract: For decades, French guinea fowl have been affected by fulminating enteritis of unclear origin. By using metagenomics, we identified a novel avian gammacoronavirus associated with this disease that is distantly related to turkey coronaviruses. Fatal respiratory diseases in humans have recently been caused by coronaviruses of animal origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 14 publications
1
37
2
Order By: Relevance
“…Quail coronavirus, which has a high spike sequence identity to TCoV, also causes enteritis with subsequent diarrhea and reduced growth in young quails (Coturmix coturmix) (Torres et al, 2013). In guinea fowl (Numida meleagris), guinea fowl coronavirus results in acute enteritis and pancreatitis (Liais et al, 2014). Other IBV(-like) coronaviruses cause respiratory and kidney diseases in pheasants (Phasianus colchicus) (Cavanagh, 2005;Gough et al, 1996), and respiratory disease and pancreatitis in pigeons (Columba livia; Qian et al, 2006).…”
Section: Infectious Bronchitismentioning
confidence: 99%
See 3 more Smart Citations
“…Quail coronavirus, which has a high spike sequence identity to TCoV, also causes enteritis with subsequent diarrhea and reduced growth in young quails (Coturmix coturmix) (Torres et al, 2013). In guinea fowl (Numida meleagris), guinea fowl coronavirus results in acute enteritis and pancreatitis (Liais et al, 2014). Other IBV(-like) coronaviruses cause respiratory and kidney diseases in pheasants (Phasianus colchicus) (Cavanagh, 2005;Gough et al, 1996), and respiratory disease and pancreatitis in pigeons (Columba livia; Qian et al, 2006).…”
Section: Infectious Bronchitismentioning
confidence: 99%
“…Scale bars represent 50 m; (C) schematic representation of the ability of recombinant trimeric spike proteins to bind to a selected set of tissues and the reported ability of the corresponding IBV strains to infect these tissues; na: data not available from literature; nd: not done. peafowl, partridge, blue-winged teal, pigeon, mallard duck, graylag goose (Cavanagh, 2005), pheasant (Cavanagh et al, 2002), guineafowl (Cavanagh, 2005;Liais et al, 2014) and various wild bird species (Chu et al, 2011). Most of these viruses have not been isolated, but were detected and partly characterized by molecular methods only.…”
Section: Spikes Of Other Avian Coronavirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although its viral origin was previously suspected, virus remained unknown. Liais et al (2014) identified a novel avian gamma coronavirus associated with this disease which was distantly related to TCoVs. To decipher the RNA virus community from turkey flocks experiencing enteric disease, Day et al (2010) analyzed turkey gut RNA virus metagenomics and demonstrated the presence of turkey-origin members of the Picornavirales, and the genus Caliciviridae, and the turkey picobirnaviruses.…”
Section: Virus Discovery and Viral Metagenomicsmentioning
confidence: 99%